Cost-effectiveness of lung cancer screening by low-dose CT in China: a micro-simulation study - Yihui Du; Yanju Li; Grigory Sidorenkov; Rozemarijn Vliegenthart; Marjolein A. Heuvelmans; Monique D. Dorrius; Harry J.M. Groen; Shiyuan Liu; Li Fan; Zhaoxiang Ye; Marcel J.W. Greuter; Geertruida H. de Bock (Journal of the National Cancer Center, 2022)
Background: The effectiveness of lung cancer screening with low-dose computed tomography (LDCT) has been established. The current study evaluates the cost-effectiveness of lung cancer screening with LDCT in a general population in China. Methods: A previously validated micro-simulation model was used to simulate a cohort of men and women on a lifetime horizon in the presence and absence of LDCT screening. The modeling data were collected from numerous national and international sources. Simulated screening scenarios included different combinations of screening intervals and start and stop ages. Additional costs (valued in Chinese Yuan, CNY; 1 USD = 6.8976 CNY, 1 EUR = 7.8755 CNY in 2020), life-years gained (LYG) and mortality reduction due to screening were also determined. The costs and life-years were discounted by 3%. All results were scaled to 1,000 individuals. The average cost-effectiveness ratio (ACER) was calculated. A willingness-to-pay threshold of CNY 217.3k / LYG was considered. A healthcare system perspective was adopted. Results: Compared to no screening, lung cancer screening by LDCT in a general Chinese population yielded 21.0 – 36.7 LYG in men and 9.2 – 16.6 LYG in women across the scenarios. For men, biennial LDCT screening yielded an ACER of CNY 171.4k – 306.3k / LYG relative to no screening. Biennial screening performed between 55 and 75 years of age was optimal at the defined threshold; it resulted in CNY 174.6k / LYG and a lung cancer mortality reduction of 9.1%, and this scenario had a 75% probability of being cost-effective. For women, the ACER ranged from CNY 364.2k to 1193.3k / LYG. Conclusions: In China, lung cancer screening with LDCT in the general population including never smokers could be cost-effective for men with 75% probability, but not for women. The optimal strategy for men would be performing biennial screening between 55 and 75 years of age.